МИТНІ РЕЖИМИ У СТИМУЛЮВАННІ ЗОВНІШНЬОЕКОНОМІЧНОЇ ДІЯЛЬНОСТІ УКРАЇНИ - Дем'янюк, Ольга Борисівна; Кекіш, Ігор Петрович (Науковий журнал «Світ фінансів», 2017)
Дем'янюк О. Б., Кекіш І. П. Митні режими у стимулюванні зовнішньоекономічної діяльності України. Проаналізовано стан зовнішньої торгівлі товарами України та наголошено на ключових факторах, що негативно позначилися на її обсягах. Визначено цілі і функції митних режимів у розвитку зовнішньоекономічних відносин та досліджено їх стимуляційний вплив на зовнішньоекономічну діяльність держави. Акцентовано увагу на ролі пільг з оподаткування товарів, що переміщуються через митний кордон, в частині збалансування інтересів держави і суб’єктів господарювання для стимулювання зовнішньоекономічної діяльності. Запропоновано рекомендації щодо активізації зовнішньої торгівлі через інститут митних режимів. Демянюк О. Б., Кекиш И. П. Таможенные режимы в стимулировании внешнеэкономической деятельности Украины. Проанализировано состояние внешней торговли товарами Украины и указаны ключевые факторы, негативно влияющие на ее объемы. Определены цели и функции таможенных режимов в развитии внешнеэкономических отношений, исследовано их стимулирующее влияние на внешнеэкономическую деятельность государства. Акцентировано внимание на роли льгот по налогообложению товаров, перемещаемых через таможенную границу, в части сбалансирования интересов государства и субъектов хозяйствования для стимулирования внешнеэкономической деятельности. Предложены рекомендации по активизации внешней торговли через институт таможенных режимов. Demianiuk O., Kekish I. Customs regime in promoting foreign economic activity of Ukraine. Introduction. One of the ways the state can employ to promote foreign economic activity is to support and motivate the entities engaged in foreign economic activity. Given the limited amount of its financial resources, the state has to support national manufacturers entering the foreign market by making use of those means and mechanisms that do not incur direct statebudget expenses. The customs regime is among such mechanisms.Purpose. The purpose of the present article is to study the facilitating impact of the customs regime used in Ukraine on the development of foreign economic activities in the context of balancing interests of the entities engaged in the foreign economic activity and the state and the foreign trade promotion.Results. The status of the foreign goods trade of Ukraine has been analysed, and the key factors negatively affecting its amount have been stressed. The goals and functions of the customs regime have been defined in the development of the foreign economic activity, and their facilitating influence on the foreign economic activity of the state has been researched. Significant attention has been paid to the role of duty exemption in relation to goods moving across the customs border in terms of balancing the interests of the state and economic entities with the aim of promoting the foreign economic activity.Conclusion. The use of a customs regime assist in constructing foreign economic activities and defining the directions of the foreign economic trade development, facilitating the foreign economic activity of the state, and developing the entities with regard to their needs and interests by establishing mutually beneficial cooperation between the economic entities and the state. When it comes to cooperation between the economic entities and the state, the awarenessbuilding effort of the customs bodies dealing with goods transfer under a concrete customs regime should be improved in order to provide the economic entities with an opportunity to choose the most suitable way of entering their goods. To improve the efficiency of the foreign economic activity, the fiscal impact of the customs duty mechanisms should be reduced, whereas the regulatory impact should be increased when imposing duties on goods being transferred across the customs border.